Museums and anthropophagy of archaeological heritage: (dis) paths of Brazilian practice - Camila de Moraes Wichers (2010) (Cadernos de Sociomuseologia, 2014)
In this thesis we seek to understand the waywardness and disagreements of the dyad Museums / Museology - Archaeological Heritage / Archaeology in Brazil, but above all we seek to identify and construct ways and common factors. We start from an historical approach to this relationship, outlining the mentality that marked the distance between Archaeology and Museology in Brazil. In a second step, we deepen the analysis of this relationships in contemporaneity, marked by a significant increase in the archaeological research, especially those related to environmental licensing of the enterprises. This indicates an approximation of the relationship between the archaeological heritage and developmental issues, implying the option of Sociomuseology. In a third step, we make an analysis of the expografic discourses of the archaeological collections and we return to the museological trials in which we operated. Finally, we apply the perspectives of Sociomuseology in socialization of the archaeological resources of Transnortheastern Railroad, one of the strategic programs of the Brazilian Government. The outlined program is understood as a synthesis of the complex but necessary relationship between Archaeology and Museology in the Brazilian contemporary scene. Thus, one way of overcoming the obstacles outlined throughout the thesis lies in the intertwining between the Sociomuseology and the Post-Processual Archaeology.Key-words: Sociomuseology – Archaeology’s Musealization – Brazilians Museums - Museologic Comunications – Post-Processual Archaeology